Aspects of British music of the 1990s - O'Hagan, Peter (Aldershot Ashgate, 2003)
The product of a conference held at the University of Surrey, Roehampton, in 1999, which brought together composers and academics in a forum in which issues of musical style and language could be addressed in context. The book focuses on the work of six composers, including Birtwistle and Harvey.